Severe Maternal Outcome in Women Admitted to an Obstetric Intensive Care Unit in the Northeast of Brazil: A Cross-Sectional Study - Flávio Xavier da Silva; Ryta de Kássia Andrade Rufino; Micaelly Barbosa Padilha; Stephanie Karoline Santos Bezerra; Mario Diego Teles Correia; Leila Katz (The Scientific World Journal)
Conclusion: SMO is a commonly occurring outcome in an obstetric ICU with great possibility of treatment. Direct obstetric causes such as hypertension syndromes, postpartum haemorrhage, and puerperal infection were the most prevalent causes in the development of this outcome. Puerperal infection was the condition most associated with SMO.